Treatment methods for fractures of the zygomatic-orbital complex - T.A.Olimjonov; D.R.Fattayeva; J.A.Umarov (Periodica Journal, 2022)
With fractures of the zygomatic-orbital complex, the lines of fractures pass through the zygomatic-alveolar crest - often at the base in the region of the alveolar process of the upper jaw; through the lower edge of the orbit - in the area of the zygomatic-maxillary suture or more medially; in the area of the zygomatic arch - along the zygomatic-temporal suture or near it; in the region of the lateral margin of the orbit, along the zygomatic-frontal suture.
Keywords: zygomatic-orbital complex; zygomatic arch; orbital deformity; osteosynthesis